Er løsningen på “menneskesøn”- problemet fundet? I anledning af Maurice Caseys nye “menneskesøn”-bog - Müller, Mogens (Dansk Teologisk Tidsskrift, 2008)
This article presents the results of Maurice Casey, The Solution to the ‘Son of Man’ Problem, and their impact on the understanding of the expression in the New Testament gospels. The probable background is seen in an Aramaic mode of speech where bar nash means nothing more than ‘man’, used by the speaker either about himself, or about himself and others, or about somebody whose identity becomes clear through the context. Thus there is nothing Messianic about the expression in itself.